The quality of service paradigm as the focus of net-centric computing: a postgraduate course - Petrova, K.; Sarkar, N.; Buchan, J (NACCQ, 2004)
In the past three years a new postgraduate elective course on Net-centric computing was developed for a Master’s degree in Information Technology. The course evolved around the core subject topics included in the Computer Science body of knowledge as suggested by the IEEE Computer Society/ACM Task Force in the Computing Curricula 2001 report, with a strong emphasis on the relationship between networking technology and the applications delivered in a global networked environment.